The Worth Of Forensic Psychology: A Review Of The Brace Character Profile As Prospects Of Criminal Profiling - Masruroh, Nur Lailatul; Purnama, D. Candra; Martatino, Ingga Yonico; Frediansyah, Andri; Dini, Fitria (Jurnal Keperawatan dan Kesehatan, 2014)
This paper showed that a prospects of criminal profiling based critical review of the BRACE character profile because potential of violent and serial crime is a growing concern in Indonesia and elsewhere. The BRACE Character Profile is a powerful analytical tool that is designed to profile the core human nature of a known or unknown subject (UNSUB), and provides a rich narrative of a subject?s profile across three domains, namely cognitive, behavioral, and existential motivational. The objectives of the current study are to briefly address the potential of offender profiling and current shortcomings, introduce the BRACE Character Profile instrument, and explain the rationale and basic methodology. A common criticism that can be addressed by the BRACE methodology is the reported lack of scientific grounding, empirically evidence, and standardization of narrative type profiles, and the ?one size fits all? approach of actuarial profiling methods. The methodology has had exposure in forensic scale activities of UNSUB profiling, psychological autopsies, cold case reviews, interrogation strategy, risk of violence determination, and defense or prosecutor strategy, but the need to qualify the usefulness in each area has to be addressed to ensure practical effectiveness and evidentiary acceptability, and entrench the methodology more widely.